Allelopathic Sugarcane Leaf Litter and Its Potential Use as Soil Mulching for Weed Management in Sugarcane Cultivation - Krumsri, Ramida; Poonpaiboonpipat, Thanatsan; Samaksaman, Ukrit; Nuengchamnong, Nitra; Laosinwattana, Chamroon (My University, 2026)
Sugarcane leaves, both green and fallen, left after harvest, are agricultural residues containing compounds that inhibit weed germination and seedling growth. This study evaluated their allelopathic effects and mulching potential for weed control. Experimental results using seeds of Ipomoea pes-tigridis and Dactyloctenium aegyptium suggest that the aqueous extract from sugarcane leaf litter reduces seedling growth. When compared to mulch made from extracted sugarcane leaves, mulch made from nonextracted leaves considerably decreased weed emergence and biomass in the pot experiment. It appears that the weed suppression was not just due to the mulching but also to the allelochemicals that were still present in the unprocessed leaves. Weed germination and seedling rates appeared to be lowered, possibly due to the presence of allelochemicals, especially phenolic compounds. Under sugarcane production conditions, field experiments were conducted to evaluate the effects of soil mulching using sugarcane leaf litter applied at rates of 4, 8 and 12 t ha−1. As a soil mulch, sugarcane leaf litter resulted in reduced weed density and biomass compared to typical agricultural practices, with weed control efficacy improving at higher rates of application. For instance, mulching rates of 8 and 12 t ha−1 resulted in respective sugarcane outputs of 104.2 and 111.6 t ha−1, whereas mechanical, manual and no weeding respectively yielded 81.25, 126.88 and 31.25 t ha−1. Based on these findings, the utilisation of sugarcane leaf litter as a soil mulch can reduce weed seed germination and growth, and can therefore be considered as an agroecological practice to be included in sustainable weed management strategies.
Keywords: bioassay; field trial; organic farming; phenolic acids; Saccharum officinarum L.; weed suppression